Literasi Digital dalam Pendidikan Agama Islam: Tantangan dan Peluang Penggunaan Teknologi dalam Pembelajaran - Siti Nurhalimah; Mulyawan Safwandy Nugraha (Jurnal Inovasi Pembelajaran dan Pendidikan, 2025)
This study examines the dynamics of digital literacy in Islamic Religious Education (Pendidikan Agama Islam/PAI) at SMK Plus Nusa Putra. The research addresses the paradox of smartphone usage in classrooms, where students demonstrate high technical proficiency yet limited ability to critically evaluate the validity of online religious content. Employing a qualitative case study approach, data were collected through participant observation, in-depth interviews with students and teachers, and document analysis. The findings reveal a phenomenon of digital authority disruption, in which social media algorithms exert greater influence on students’ religious perspectives than formal educators. Despite these challenges, the study identifies significant opportunities for developing a “future classroom” model that transforms complex religious concepts into accessible visual and digital formats. The study concludes that the effectiveness of PAI in the digital era depends on students’ critical thinking and digital tabayyun skills, with teachers assuming the role of digital curators. Strategic recommendations include integrating digital ethics into the school curriculum to foster both professional competence and spiritual resilience in an increasingly globalized information environment.